Scalable Solvent-Based Fabrication of Thermo-Responsive Polymer Nanocomposites for Battery Safety Regulation. Issue 8 (6th August 2021) - Li, Mingqian; Xu, Panpan; Lee, Suk-woo; Jung, Bum-young; Chen, Zheng
Abstract : Improving lithium-ion battery (LIB) safety remains a challenging task when compared with the tremendous progress made in their performance in recent years. Embedding thermo-responsive polymer switching materials (TRPS) into LIB cells has been proved to be a promising strategy to provide consistent thermal abuse protections at the coin-cell level. However, it is unrealistic to achieve large-scale applications without further demonstration in high-capacity pouch cells. Here, we employed tungsten carbide as a novel conductive filler, and successfully overcame the intrinsic processing difficulty of polyethylene matrix in a scalable solvent-based method to obtain ultra-thin, uniform, highly conductive TRPS. Moreover, by integrating TRPS directly into LIB electrodes, no extra fabrication facilities or processes are required for making the cells. As a result, multi-layer pouch cells with consistent electrochemical performance and thermal abuse protection function were fabricated using industry-relevant manufacturing techniques, which brings TRPS one step further to the real application scenarios.